O2 linear-onset kinetics spanning steady- and non-steady-state exercise - Robergs, R.; O`Malley, B.; Dewilde, A.; D`Auria, S.; Krouzecky, A. (Frontiers in Physiology, 2025)
Introduction: The traditional method for quantifying the kinetics of the increase in the body`s consumption of oxygen (VO2) during exercise transitions to steady state involves application of a mono-exponential function. Anomalies exist to question the validity of this method, as they show the initial (~1 min) of this VO2 response is linear.